Approximating an advanced multi-dimensional reciprocal-quadratic mapping via a fixed point approach - Beri V. Senthil Kumar; Hemen Dutta; S. Sabarinathan (Boletim da Sociedade Paranaense de Matemática, 2022)
There are many results on stability of various forms of functional equations available in the theory of functional equations. The intention of this paper is to introduce an advanced and a new multi-dimensional reciprocal-quadratic functional equation involving $p>1$ variables. It is interesting to note that it has two different solutions, namely, quadratic and multiplicative inverse quadratic functions. We solve its various stability problems in the setting of non-zero real numbers and non-Archimedean fields via fixed point approach.